2009
DOI: 10.1111/j.1538-7836.2009.03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet size distinguishes between inherited macrothrombocytopenias and immune thrombocytopenia

Abstract: Summary. Background: Distinguishing inherited thrombocytopenias from immune thrombocytopenia (ITP) can be difficult, and patients are therefore at risk of misdiagnosis and inappropriate treatments. Although it is known that the most common inherited forms of thrombocytopenia are characterized by increased platelet size, the diagnostic power of this feature has never been investigated. Objectives: The aim of this study was to test the hypothesis that platelet size can be used to differentiate ITP from inherited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 12 publications
(8 reference statements)
4
99
3
4
Order By: Relevance
“…They reported that platelets were larger in inherited macrothrombocytopenias than in ITP. Combining MPD with MPV increased sensitivity and specificity of macrothrombocytopenia diagnosis to 0.97 and 0.89, respectively [17]. In our study too, the MPV in patients with macrothrombocytopenia was significantly higher (p \ 0.00001) than that seen in patients with ITP and secondary thrombocytopenia.…”
Section: Discussionsupporting
confidence: 55%
“…They reported that platelets were larger in inherited macrothrombocytopenias than in ITP. Combining MPD with MPV increased sensitivity and specificity of macrothrombocytopenia diagnosis to 0.97 and 0.89, respectively [17]. In our study too, the MPV in patients with macrothrombocytopenia was significantly higher (p \ 0.00001) than that seen in patients with ITP and secondary thrombocytopenia.…”
Section: Discussionsupporting
confidence: 55%
“…The first study found that an MPD larger than 3.3 mm differentiated MYH9-RT, mBSS, and bBSS from ITP with 89% sensitivity and 88% specificity. 7 The second study, evaluating a different patient population, found that the same cutoff value had 67% specificity and 75% sensitivity in differentiating these conditions from ITP. 5 This study confirmed that MPD has good diagnostic accuracy in distinguishing ITs with giant platelets (hMYH9-RD, tMYH9-RD, and bBSS) not only from ITP but also from all other ITs.…”
Section: Discussionmentioning
confidence: 99%
“…On average, 200 platelets were evaluated in each patient, and the maximum diameter of each platelet was recorded. 7 Platelets in clumps or those with extending pseudopodia were not considered. Technicians who measured the diameters were blinded to the patients' diagnoses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since electronic counters greatly underestimate both platelet count and volume in subjects with MYH9-RD, 18 platelet counts were also evaluated by phase-contrast microscopy in a counting chamber, and platelet size was measured by software-assisted microscopy examination of peripheral blood films. 19 Only platelet counts measured by microscopy were used for the purposes of this study.…”
Section: Assessments and Outcome Measuresmentioning
confidence: 99%